2021
DOI: 10.3390/jcm11010164
|View full text |Cite
|
Sign up to set email alerts
|

Validation of Noninvasive Remote Dielectric Sensing System to Quantify Lung Fluid Levels

Abstract: Background: The accuracy of the remote dielectric sensing (ReDSTM) system, which is a noninvasive electromagnetic-based technology to quantify lung fluid levels, particularly among those with small body size, remains uncertain. Methods: Hospitalized patients with and without heart failure underwent assessment of lung fluid levels with ReDS and successive chest computed tomography imaging. We performed a correlation analysis of the ReDS measurement, representing lung fluid levels, and computed tomography-derive… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
19
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

4
4

Authors

Journals

citations
Cited by 24 publications
(23 citation statements)
references
References 20 publications
(25 reference statements)
0
19
0
Order By: Relevance
“…The ReDS system is a novel noninvasive tool used to quantify lung fluid volume, which correlates well with intracardiac filling pressures by right heart catheterization and intraparenchymal fluid using high resolution computed tomography, when measured at rest condition [ 5 , 6 , 11 ]. The prognostic impact of ReDS values measured at rest condition was previously investigated [ 12 ].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The ReDS system is a novel noninvasive tool used to quantify lung fluid volume, which correlates well with intracardiac filling pressures by right heart catheterization and intraparenchymal fluid using high resolution computed tomography, when measured at rest condition [ 5 , 6 , 11 ]. The prognostic impact of ReDS values measured at rest condition was previously investigated [ 12 ].…”
Section: Discussionmentioning
confidence: 99%
“…Prior data has suggested that lung fluid volume levels measured with ReDS ( Figure 1 ) correlate with pulmonary capillary wedge pressure in patients with HfrEF [ 5 ]. The ReDS system additionally has been shown to quantify lung fluid volume levels, with a resolution comparable to chest imaging with computerized tomography [ 6 ].…”
Section: Introductionmentioning
confidence: 99%
“…Recently, remote dielectric sensing (ReDS TM , Sensible Medical Innovations Ltd., Netanya, Israel) system, which is a noninvasive electromagnetic-based technology to quantify lung fluid volume, has been introduced in the clinical setting (Figure 2) [21]. Prior work has demonstrated the correlation between ReDS value and lung fluid level measured by high-resolution computed tomography [22,23]. The ReDS system is a promising tool to accurately assess for pulmonary congestion and may be an appropriate precursor modality to screen for patients that may benefit from early ASV therapy when decompensated heart failure is suspected.…”
Section: Adjustment Of Adaptive Servo-ventilation Therapymentioning
confidence: 99%
“…ReDS is a novel device that can estimate lung fluid levels noninvasively, quickly, and easily [5]. ReDS value had a strong correlation with the degree of pulmonary congestion quantified by computed tomography using unique software [8,9]. We initiated the use of this device before Japanese commercial marketing, and this is an initial in which ReDS values were measured during hemodialysis.…”
Section: Lung Fluid Assessmentmentioning
confidence: 99%
“…The received signals, after passing through the tissue, indicate the lungs' fluid content [5]. The ReDS value correlates with the degree of pulmonary congestion quantified by computed tomography in patients with and without heart failure, regardless of body size, although it is expected to be affected by electrodes, body habitus, fat content, and skin moisture [8,9]. The normal range of ReDS values suggested by the manufacturer is 20-35%.…”
Section: Introductionmentioning
confidence: 99%